Usage pédagogique des analogies dans l’enseignement supérieur - Stéphanie Naud; Emmanuel Sander; Kalliopi Benetos (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Necessary for learning, intuitive conceptions constrain the construction of new conceptions. "Argumentation by Analogy" has been developed as a pedagogical device to support students' conceptual change. Activities supported by digital technologies aim to make the intuitive conceptions mobilised by students through analogies explicit and to point out their limits through alternative analogies. The purpose of this paper is to report on the effects of the pedagogical use of analogies on teaching in a university context. Our hypotheses are tested in three studies using data collected from master's and first-year bachelor's students in education sciences. Results obtained from the qualitative (properties of the notion mobilised; nature of the similarities) and quantitative analyses make it possible to affirm that the ability to produce an analogy and the nature of its content qualify students’ mastery of the notion in question. Thus, collecting the students' conceptions of notions addressed through the production of analogies gives the teacher a precise vision of the degree to which these notions are acquired. The pedagogical design "Argumentation by Analogy" makes analogies used informally conscious and explicit so that they become a formal basis for the construction of new knowledge.